The effects of the AIDS epidemic on the safety of the nation's blood supply. - Petricciani, J C (1988)
Present safeguards for the blood supply consist of three tiers of protection: donor deferral based on a donor's history of risk factors, confidential exclusion of blood units from donors with self-admitted risk factors, and testing of the blood itself. Before the discovery of the AIDS virus in 1983 and 1984, there was no specific test relevant to AIDS that could be used to help improve the safety of the blood supply. The first step was intensified efforts, based on what was then known of the epidemiology of the disease, to take donor histories to identify risk factors. The first specific tests were for the detection of antibodies to the virus and came into use in 1985. The general features of AIDS are described, together with the scientific rationale for the various types of laboratory tests, those for the virus itself, antigens, antibodies, the genetic material of the virus, and T4 lymphocytes. General characteristics of the tests are reviewed. Since testing began, about 30 million units each of blood and plasma have been screened. More than 3,000 infected persons in the blood donor group have been identified as HIV-antibody positive. Thirteen cases of transfusion-associated infection have been documented. They are believed to have occurred because a detectable level of antibodies had not yet formed in the infected donors. Currently, such transmission is thought to occur once in about 40,000 to 250,000 donations, a dramatic improvement from 1983.